DEVELOPMENT OF TEACHING MODULES BASED ON SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY) TO IMPROVE STUDENTS CRITICAL THINKING SKILLS IN GREEN CHEMISTRY MATERIAL - Anisa Nabilah; Mitarlis (Universitas Negeri Surabaya, 2026)
This study aims to describe the feasibility of teaching modules based on SETS (Science, Environment, Technology, Society) to improve students’ critical thinking skills in green chemistry material. This study uses Thiagarajan’s 4D development research method with modifications from Ibrahim’s 3D method, which includes the define, design, and develop stages. Feasibility was assessed based on three aspects: validity, practicality, and effectiveness. Validity was assessed in terms of content and construct validity. Overall, in terms of content and construct validity, the module received a mode of 3 and 4, which are categorized as good and very good. Furthermore, practicality was reviewed from the student response questionnaire, which obtained an average of 94.81% in the excellent category, supported by the results of student activity observations of 89.04%, which showed active involvement in each stage of learning, and learning implementation of 97.65%, which confirmed that the entire series of activities was carried out very well. Meanwhile, the effectiveness of the teaching module based on SETS (Science, Environment, Technology, Society) can be seen from the increase in the average critical thinking skills test score from 28.72 to 83.86 with an average N-gain of 0.7718, which is in the high category. The Wilcoxon test results showed that all students experienced a significant increase (Z = -5.235; Sig. 0.000 < 0.05). Thus, the teaching module based on SETS was declared effective in improving students’ critical thinking skills in green chemistry material.